Labor Relations, Labor Relations Law and Public Policy - Montague, J. (Relations industrielles / Industrial Relations, 1964)
In this address the author explains how and why, legislation in Canada appears to have compartmentalized its own activities within the labour market so that a number of legislative efforts are continued through the economy with little relationship one to the other.** This paper tvas presented at the First Meeting of the Canadian IndustrialRelations Research Institute, held at McGill University, July 6th, 1964.